Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Test - Page 578: 22



Work Step by Step

Simplify. $ (\sqrt{x+9}-\sqrt {x-7})=2$ Take square on both sides. we have, $ (\sqrt{x+9}-\sqrt {x-7})^2=2^2$ or, $(x+9)^2+(x-7)^2+2 (\sqrt{x+9}+\sqrt {x-7})=4$ or, $2x-2=-2 (\sqrt{x+9}+\sqrt {x -7})$ Thus, $x^2-2x+1=x^2+2x-63$ $-4x=-64$ Hence, we can conclude that $x=16$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.